The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1016/s0006-3223(99)00114-6
|View full text |Cite
|
Sign up to set email alerts
|

22q11 deletion syndrome: a genetic subtype of schizophrenia

Abstract: Schizophrenia is likely to be caused by several susceptibility genes and may have environmental factors that interact with susceptibility genes and/or nongenetic causes. Recent evidence supports the likelihood that 22q11 Deletion Syndrome (22qDS) represents an identifiable genetic subtype of schizophrenia. 22qDS is an under-recognized genetic syndrome associated with microdeletions on chromosome 22 and a variable expression that often includes mild congenital dysmorphic features, hypernasal speech, and learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
231
0
28

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(264 citation statements)
references
References 98 publications
(124 reference statements)
5
231
0
28
Order By: Relevance
“…12,13,19,20,[60][61][62] They are especially interesting as the same regions may encompass susceptibility genes for schizophrenia. [63][64][65][66][67][68][69][70] Park et al 71 made similar conclusions in a study of psychotic BD in which most areas of linkage overlapped with those reported in previous investigations of schizophrenia.…”
Section: Psychotic Symptoms In Bdsupporting
confidence: 71%
“…12,13,19,20,[60][61][62] They are especially interesting as the same regions may encompass susceptibility genes for schizophrenia. [63][64][65][66][67][68][69][70] Park et al 71 made similar conclusions in a study of psychotic BD in which most areas of linkage overlapped with those reported in previous investigations of schizophrenia.…”
Section: Psychotic Symptoms In Bdsupporting
confidence: 71%
“…Classically associated features include mild facial dysmorphic features, learning difficulties, hypernasal speech, and congenital anomalies such as congenital heart defects and velopharyngeal insufficiency and/or submucous cleft palate [3]. Overt cleft palate is rare in 22qDS [2••].…”
Section: Common Features and Prevalence Of 22qdsmentioning
confidence: 99%
“…Thus, many studies of schizophrenia would have inclusion and exclusion criteria and sampling strategies that would bias against ascertainment of individuals with 22qDS. However, high rates of 22qDS result from screening for patients with physical features of the syndrome and/or borderline to mild mental retardation [3] or childhood-onset schizophrenia (Table 1).…”
Section: How Common Is 22qds In Schizophrenia?mentioning
confidence: 99%
“…Possibly, ASDs overlap with other disorders, such as the 22q11.2 deletion, in only a few specific subgroups. Subsequent studies should explore this possibility in order to increase our knowledge of potential genetic subtypes of autism (Bassett & Chow, 1999;cf. Ogilvie et al, 2000).…”
Section: Implications and Future Directionsmentioning
confidence: 99%